Liability of Commercial Air Transport Service Providers in the Carriage of Corpse - Yunita Sabrie , Hilda; Fillipo Taufik, Harven; Maharani Tanusaputri, Anita; Maradona, (International Journal of Scientific Research and Management (IJSRM), 2023)
In general, objects in air transportation are passengers, baggage, cargo, and/or post. However, in its development, the existing air transportation also carries out the transportation of corpses. If it is related to the responsibility of the air carrier, then the position of the corpse in air transport is important to be studied in order to determine the form and limits of the air carrier's responsibility. Therefore, this study aims to discuss the position of the corpse in the law of air transportation, as well as the responsibility of the carrier in transporting the corpse by air. The method used in this research is legal research with conceptual approach, statutory approach, comparative approach, and case approach. Based on the research that has been done, it can be found that the position of the corpse in international and national air transportation law has been positioned as cargo. Consequently, the responsibility of the air carrier in the transportation of corpses is also based on the responsibility of the carrier in the carriage of cargo. This is of course inappropriate when applied to the transportation of corpses, because with such arrangements, heavier body will receive greater compensation than lighter body.Keywords: air transportation; corpse; responsibility; legal protection.